Predicting factors of job satisfaction through organizational culture: A case of Malaysian private learning institution - Chan, Tak Jie; Wong, Elizabeth; Wok, Saodah (Universiti Kebangsaan Malaysia, 2017)
The paper attempts to explore the dimensions of organizational culture and job satisfaction among employees in one of the private learning institutions in Malaysia. The study utilized Organizational Culture Index (OCI) developed by Wallach (1983), which comprised of bureaucratic, innovative, and supportive cultures. Multistage sampling has been used to select the sample for the survey designed. Questionnaires were distributed to 118 employees, however, only 77 yielded valid responses. The data were then analyzed with the Pearson-Product Moment Correlation test and Multiple Regression tests using the enter method through the Statistical Package for the Social Sciences (SPSS) version 22.0. The findings of the study show that bureaucratic organizational culture has a positive and a moderate relationship with job satisfaction, while, innovative and supportive organizational cultures have positive and high relationships with job satisfaction. In addition, multiple regression analysis indicates that innovative and bureaucratic organizational cultures are the predictors that enhance job satisfaction among the employees in the current private learning institution. Hence, this had called upon the management of the particular learning institutions to foster on innovative and bureaucratic organizational cultures in order to enhance the employees’ job satisfaction that will result in higher organization’s productivity. Further study to replicate the research in various industries in Malaysia to explore more on the employees’ job satisfaction is suggested. Future studies can also examine organizational culture with other variables such as leadership style, organizational commitment, and employee engagement in the Malaysian setting.